Landslide model using OpenFOAM applied to the area of Pamplona, Colombia (BISTUA Revista de la Facultad de Ciencias Básicas, 2022)
Catastrophic events have different origins, some of them happened in natural way and some others due to failures in facility or equipment created by human beings. Among the natural catastrophic events are landslides. It is widely known that landslides and debris flows are triggered by geological movements or heavy rainfall. Due to their geological, geomorphological and climatic configuration, some regions are more prone to the happening of this type of phenomena. In this study field, research has focused on the development of landslide prediction technology. In this work, a superficial landslide product of rains is simulated in which the geomaterial involved in the landslide can be modeled as a fluid, measurements are taken on the ground spot using a digital DEM elevation map and the characteristic parameters of the soil are obtained by means of seismic prospecting techniques, finally a rheological model is implemented which adapts to soil conditions and the OpenFOAM software is used to model a landslide in the km 1 zone via Bucaramanga, Pamplona Norte de Santander, where the extension of propagation of a possible landslide over the University of Pamplona is shown.